Implementing Smart Classroom Innovations to Enhance Elementary Education Quality in Rural Areas with a Case Study of SD Negeri 173637 Narumonda - Marpaung, T.J.; Manurung, Asima; Erwin (Talenta Publisher, 2025)
Education in rural areas faces challenges such as limited access to technology and outdated teaching methods, hindering student engagement and learning outcomes. This study implements a Smart Classroom initiative at SD Negeri 173637 Narumonda, North Sumatra, aiming to improve educational quality through digital tools and interactive teaching in line with Society 5.0 principles. The project began with observations and a Focus Group Discussion (FGD) to assess the school’s readiness. Findings revealed limited technological resources and low teacher proficiency in digital tools but high enthusiasm from students and a positive attitude from teachers. The initiative introduced Android TVs, sound systems, and teacher training on digital pedagogy and Moodle-based e-learning. Initial results show increased student engagement and improved teacher confidence in using technology, despite concerns about sustainability and curriculum adaptation. The program demonstrates the potential of collaboration between educational institutions and communities in transforming rural education. It serves as a scalable model for addressing educational disparities and aligns with Sustainable Development Goals (SDGs), particularly Goal 4 on quality education.